(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Azilsartan AT2 receptor antagonist was designed for the investigation on memory enhancing activity. Azilsartan is used to treat high blood pressure. Azilsartan belong to a class of drug called Angiotensin receptor blockers (ARBs). Scopolamine (0.4mg/kg I.P) was administered to induce amnesia. Scopolamine is muscaranic receptor antagonist with amnesia properties that have been used for decades in experimental rats to induce impairment in their performance of a variety of tasks requiring intact working and reference memory piracetam dose of (400mg/kg I.P) was used as a standard drug. The azilsartan dose (10mg/kg and 20mg/kg P.O) was prepared by mixing the suitable amount of drug in normal distilled water to make for oral administration. Azilsartan was studied for investigation of memory enhancing activity by using scopolamine induced amnesia as interoceptive model and Morris water maze (MWM) test and elevated plus maze (EPM) test as exteroceptive model. The two were selected for oral administration of azilsartan. The azilsartan (10mg/kg and 20mg/kg) for this study NO effect of memory enhancement was recorded for test drug by MWM&EPM test because azilsartan treated rats manifested increases in escape latency time (ELT) and decrease in time does not possess memory (TSTQ) in MWM test and increase in transfer latency time does not possess memory enhancing effect against scopolamine induced amnesia using both model. The present study signalized that azilsartan does not possess memory enhancing activity.